AKUNTANSI MANAJEMEN DALAM FILSAFAT ILMU - Rosita, Rosita; Rachmawati K, Ida Ayu Kade (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
The early presence of philosophy and science because of radical,systematic and universal thinking processes. Philosophy aims to gainknowledge of the truth. It is also related to the development of accountingscience.Philosophy has an object, function, usefulness and a scientificapproach. The scientific approach consists of ontology, epistemology andaxiology. In the development of management accounting science that is partof the science of accounting also has ontology, epistemology andaxiology.Ontology in management accounting science is a belief that it is partof the universe. The science of epistemology management accountingexamines and tries to discover the characteristics of management accountingscience. For axiology explain the usefulness of management accountingscience in human life.